Aransemen Kroncong Lagu Sasak Gugur Mayang - Yuspianal Imtihan; Hary Murcahyanto; Abdullah Muzakkar; Lalu Ahmad Alfian Bakti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
ABSTRACT This paper is based on the results of research which aims to describe the form of the keroncong version of the keroncong version of the traditional song Gugur Mayang arrangements. Descriptive qualitative method with a phenomenological approach is used in data collection through observation, interviews and documentation with a focus on the form of keroncong arrangements in the song Gugur Mayang. The uniqueness of this paper is the scarcity of research on traditional Sasak songs arranged in the kroncong version that has been researched by other researchers. The results of this study indicate that the form of the arrangement of the keroncong version of the song Gugur Mayangis a song that begins with the AA section, with the introduction at the beginning of the song, then the bridge, followed by the AA” section on the song Gugur Mayang. In the episode or interlude, it is filled with violins and accompanied by several other instruments then it is entered in the coda section which is played by all instruments other than the flute. The scale used in this arrangement is the D minor scale which means 1 mol or F major. Keywords: Arrangement, Gugur Mayang, Keroncong, Sasak Song.